PENGARUH LABA DAN ARUS KAS TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Kismadianto, Alvius Dwi (Jurnal Riset Mahasiswa Akuntansi, 2014)
The aim of this research is to know the influence of profit and cash flow toward share price. The researcher uses double regression linear method, because it suitable with the aim of this research which is to analyze the influence of independent variable toward dependent variable. Independent variable is net profit whereas the dependent variable is net profit whereas the dependent variable is share price. This research had done in manufacture company which is listed in Indonesia stock exchange. The selection of company’s criteria using purpose method sampling and the result showed that there were 30 companies in five periods (2008-2009). The result of this research shows that the net profit has negative influence to share price whereas cash flow has positive influence. The whole result shows that profit and cash flow influence share price for the next researcher is better to use the length of research’s period more than five years and add other research’s variables to make a research in different company.